Depression, anxiety, and physical activity among antenatal women during COVID-19 pandemic - Siti Roshaidai Mohd Arifin; Seri Wardah Zulkifli; Khadijah Hasanah Abang Abdullah; Fathima Begum Syed Mohideen; Nurul Ain Hidayah Abas; Asma Perveen; Rohayah Husain; Khairi Che Mat; Karimah Hanim Abd Aziz; Edre Mohamad Aidid; Ramli Musa; Izazol Idris (International Journal of Public Health Science (IJPHS), 2022)
The prevalence of mental health problems among antenatal women has escalated during the COVID-19 pandemic compared to the pre-pandemic period. Physical activity palys role to reduce depression and anxiety, which required to be studied further. This study aimed to assess the association between physical activity with depression and anxiety among antenatal women during the COVID-19 pandemic. This cross-sectional study applied convenience sampling to recruit 544 antenatal women from March to June 2021. Questionnaires including the Edinburgh postnatal depression scale (EPDS), state-trait anxiety inventory (STAI), and pregnancy physical activity questionnaire (PPAQ) were distributed via social media to determine the prevalence of depression, anxiety, and physical activity level. Data were analysed using descriptive statistics, chi-square, mann-whitney, and kruskal wallis tests. Out of 544 antenatal women, 24.1% of them had depressive symptoms and 82.4% had anxiety. Only 12.1% of the women were sufficiently active during the pandemic. There was no association between physical activity, depression, and anxiety. The high prevalence of depression and anxiety during the COVID-19 pandemic among Malaysian antenatal women underscores the urgent need for addressing this public health burden. Interventions to alleviate the symptoms should include strategies beyond physical activity, for example, a mobile application or telephone-delivered social support that is made easily accessible throughout the pandemic.